Analisis Keuntungan Usaha Gula Kelapa Skala Rumah Tangga di Kecamatan Segedong Kabupaten Mempawah - Pratiwi, Bella; Kusrini, Novira; Hidayat, Rakhmad (Fakultas Pertanian Universitas Tanjungpura, 2023)
This study aims to determine the magnitude of profits from the business of household-scale coconut sugar in Segedong District Mempawah District. Population in this research is coconut sugar business household scale and selected purposive (intentionally). Data analyst techniques used are total cost, revenue and profit. The results of this study indicate that based on the results of the analysis of the calculation of costs used in the business of coconut sugar household scale. The level of profit of coconut sugar business is Rp. Rp.73.585/day and Rp.1.600/Kg. The analysis shows that this household-scale coconut sugar business is profitable